Way of life and language in Wittgenstein - Defez, Antoni (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This paper analyzes the significance and philosophical use that Wittgenstein gave in his mature thought to the concept of form of life. Thus, although it is pointed out that Wittgenstein only made use of this concept in the context of the justification of linguistic praxis as an epistemological limit, it is emphasized however that in that use it is already possible to glimpse a certain anthropological conception about human beings as animals of expressive, intentional, symbolic and linguistic behavior generator of rules and lover of regularities. The article ends with an analysis of the problem of the form of life of animals and its relationship with the human form of life. In particular it highlights the linguistic and cultural character of the human form of life, and shows the limits in the attribution to the nonhuman animals of the human mental predicates.
Keywords: Wittgenstein; language; form of life; linguistic justification; instinctive behavior; animals